OPTIMIZATION OF THE OPTICAL DISTRIBUTION CABINET ON THE OPTICAL DISTRIBUTION POINT LINE USING THE INTEGER LINEAR PROGRAMMING (ILP) METHOD - Kurnia, Hibarkah; Nuryono, Arif; Wiyatno, Tri Ngudi; Sulaeman, Asep Arwan; Zulkarnaen, Iskandar (JEMIS (Journal of Engineering & Management in Industrial System), 2026)
The continuous use of software and hardware network resources results in overlapping installations at work, which results in uncontrolled operational costs in densely populated conditions, which becomes a dilemma if the arrangement is not organized. This study aims to optimize the position of the Optical Distribution Cabinet (ODC) and Optical Distribution Point (ODP) distribution lines in a distributed Fiber to the Home (FTTH) network as well as the position of customer placement on the ODP, so that the use of fibre optic cables can be minimized. This research method uses a combination of FTTH and Integer Linear Programming (ILP) where the data processing uses LINGO software. The results show that the optimal FTTH network configuration uses a 12-core fibre optic cable, ODP 1:8 passive splitters, and ODC 1:4 splitters. The proposed optimization model successfully reduced the total network deployment cost from Rp78,205,400 to Rp49,085,400, resulting in a cost efficiency improvement of approximately 59.37%. The findings also indicate that the ODP 1:8 configuration is more preferable than ODP 1:4 because it requires fewer cables, reduces network complexity, improves spatial aesthetics, and provides better scalability for future customer expansion. The practical implication of this study is that the proposed ILP-based optimization model can support telecommunications companies in designing FTTH infrastructure more efficiently, reducing installation and maintenance costs, minimizing unnecessary cable deployment, and improving long-term network scalability in densely populated urban environments. The model can also serve as a decision-support tool for future FTTH network expansion planning and infrastructure investment strategies.